Accounting Information and Digital transformation: The case of services organizations - Kartalis, Nikolaos; Veletzas, Ioannis; Broni, Georgia; Ginoglou, Emmanouil (International Conference on Business and Economics - Hellenic Open University, 2023)
Services organizations increasingly transforming themselves into digital entities by introducing innovate service and exploiting digital technologies. Not much research had been done in previous years concerning the adaption of digital transformation using the accounting information. In this article we try to investigate the role of the accounting information in digital transformation in service companies taking into account the empirical findings from a survey of 45 managers of worldwide entities. The findings shows that the accounting information plays a significant role in decision making process in service organizations and the digital technologies such as social media, internet analytics and artificial intelligence have been intensively used in contemporary businesses. JEL CLASSIFICATION CODES : M40, M41. Keywords: Accounting, Management Accounting